PENERAPAN PEMBELAJARAN ILMU TAJWID UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN PADA SISWA KELAS VII MTS DI PONDOK PESANTREN BABUL UMAM HAJORAN KEC. SUNGAI KANAN - Hasnah Azhari (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
Tajwid is a scientific field that investigates the correct method of pronouncing the Qur'an, including intonation and pronunciation. The aim of studying the science of Tajweed is to be proficient in reading the Book of Allah SWT accurately, as exemplified by the Prophet Muhammad SAW who was able to read the verses of the Book of Allah easily and precisely. This research is based on the efforts of an educator in teaching Tajweed with the aim of improving Al-Qur'an literacy skills. -Their Koran. This research aims to determine methods that can be used to teach recitation so that students at the Babul Umam Islamic Boarding School can understand the Al-Qur'an well and correctly. This research is a type of qualitative research that collects data through interviews and observations. The research method produces descriptive data in both written and oral form. The results of the research show that learning recitation helps the students of the Babul Umam Islamic Boarding School understand the Qur'an better